Signs of the wali - Christomy, Tommy (ANU E Press, 2008)
Introduction –Signs in the valley –Manuscripts in Pamijahan: Kakantun Karuhun –The Babad Pamijahan: Sunda, Java and the identity of the Pamijahanese –Karuhun, space, place and narratives –Linking to the wider worlds of Sufism –Grasping the Wali's teaching –Tapping a blessing in the house a young Sufi –Pilgrimage at Pamijahan: practice and narrative –Conclusion.
Includes bibliographical references (pages 211-217)
Keywords: Electronic books; Islam and culture; Muslim saints; Islamic shrines; Sundanese (Indonesian people); Sundanese literature; Saints in literature; Humanities; Religion and beliefs; RELIGION; Islam; General; Sundanese (Indonesian people); Rites and ceremonies; Criticism; interpretation; etc